Managerial, cultural, intelligence, marketing agility, and firm innovation - LAI,, Zhenzhu (Institutional Knowledge at Singapore Management University, 2022)
This dissertation aims to investigate the relationship between managerial cultural intelligence, marketing agility and innovation capability of foreign subsidiaries. Based on upper echelons theory (UET), I argue that managerial cultural intelligence facilitates marketing agility. Moreover, marketing agility is positively associated with innovation capability of foreign subsidiaries. Using two-wave survey data of 110 foreign subsidiaries in China, this study verified the theoretical model. It is found that managerial cultural intelligence is positively associated with marketing agility, and marketing agility is positively related to innovation capability of foreign subsidiaries. Organizational learning climate, market competition, market turbulence, and market complexity have positive moderating effects on the relationship between managerial cultural intelligence and marketing agility. This dissertation aims to enrich the research on the upper echelons theory, cultural intelligence, marketing agility and innovation capability, and provide references for foreign subsidiaries to improve marketing agility and innovation capability.